If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 3x + -5 Reorder the terms: -2 = -5 + 3x Solving -2 = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + -3x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + -3x = -5 + 0 -2 + -3x = -5 Add '2' to each side of the equation. -2 + 2 + -3x = -5 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = -5 + 2 -3x = -5 + 2 Combine like terms: -5 + 2 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 4c+11=83 | | n^2=5n+14 | | -3+y=x+6 | | -3+yi=x+6i | | 5(v+4)=8v+17 | | x/8=x/12+1/3 | | d/4 | | 8(-2x-4)+12=-54 | | b+2(9-3b)=3/4(-8b+12) | | 8x+-7=5x+8 | | 5(7x+3)-10x=115 | | -8/24=5/12 | | 6(4-2h)=4(5-5h) | | 9(x+2)-11=88 | | -9(d+2)=4(5+d) | | 5+2(4-x)=-13 | | 4y+10=3y-5 | | 3(7+2w)=1/2(-2-10w) | | -4r+6r+5a-4r= | | 3a+4=a+15 | | z=y-6 | | 4(x+10)=72 | | (x-1)(x+1)-3x(x-1)=0 | | (x-1)(x-1)-3x(x-1)=0 | | 4(x+10)=10 | | 8-t=45 | | (108/12)2 | | (-6x^3y^6)(7xy^2)= | | 4x-12y=6 | | 2(m+4)-5=2m+3 | | 1(-7-5-10v)= | | 4/3x+1=-4-2w |